Challenges and gaps in the quality of Onshore and Offshore employee transportation: a bibliometric review using Proknow-C - Ribeiro, Ana Beatriz; Detino, Junior Soares; Silva Junior, Orlando Marques da; Xavier, Thiago Padovani; Servare Junior, Marcos Wagner Jesus; Souza, Noéle Bissoli Perini de (Brazilian Journal of Production Engineering, 2025)
The article presents a comparative bibliometric review between onshore (road) and offshore (air) employee transportation modes in Brazil, using the ProKnow C methodology to select a portfolio of 12 relevant articles. The analysis highlighted the Revista Transportes as the most relevant source, despite its smaller initial volume of publications, and identified research gaps, such as the lack of studies on onshore road transportation of employees and the quality of services in offshore transportation. The results showed that onshore transportation faces challenges related to comfort, punctuality, and cost-effectiveness, while offshore transportation is more associated with operational safety and logistical complexity. Both modes are impacted by factors such as infrastructure, weather conditions, and risk management, but there is a lack of specific studies on road freight transportation of employees onshore and the quality of services provided offshore. These gaps represent opportunities for future research aimed at optimizing and continuously improving these processes.
Keywords: Employee satisfaction; Energy efficiency; Transportation management; Service quality; Corporate mobility